Studi Komparasi Pemikiran Al-Ghazali Dan Ibnu Al-Haytham Tentang Konsep Kebahagiaan - Dika, Andika; Iqbal, Adi (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
The problem raised in this study is the differences and similarities in the thoughts of Al Ghazali and Ibnu Al Haytham regarding the concept of happiness, and how these two figures contribute to the understanding of happiness in the context of Islamic thought. The purpose of this study is to analyze and compare the views of these two figures with a focus on the source of happiness, the approaches used, and the importance of balance in life. The method used in this study is qualitative analysis with a comparative method. The results of this study show that Al Ghazali emphasizes that true happiness comes from closeness to God and spiritual pursuits, while Ibn Al Haytham focuses on the search for knowledge and scientific understanding as a path to happiness. Despite these differences and approaches, both agree on the importance of balance in life, where Al Ghazali highlights the balance between spiritual and worldly aspects, while Ibn Al Haytham emphasizes the balance between intellectual and physical needs. The conclusion of this study is that the thoughts of Al Ghazali and Ibn Al Haytham, although coming from different backgrounds, complement each other in providing insights into happiness. By combining spiritual and intellectual dimensions, the understanding of happiness in the context of Islamic thought becomes more holistic and becomes a reference for individuals in seeking true happiness.